KARAKTERISTIK RAGAM BAHASA HUKUM DALAM PERSIDANGAN DI PENGADILAN NEGERI BANDA ACEH - Rahmad Nuthihar; Mursyidin; Wahdaniah (Jurnal Metamorfosa, 2020)
The focus of this study examined the characteristics of the variety of law languages found in trials at the Banda Aceh District Court. This research is a qualitative type with a qualitative descriptive approach. Data was collected by recording technique and recording the speech of trial participants consisting of judges, public prosecutors, lawyers, defendants, and visitors to the trial. The results of this study concluded that in the trial at the Banda Aceh District Court there were four characteristics of a variety of law languages consisting of, official, honesty, cohesiveness, and clarity of meaning. The characteristics of the various law languages aspects of officiality are characterized by the use of standard vocabulary words. The aspect of clarity of meaning in the trial is evidenced by the use of diction which is easily understood. The diction used by judges, lawyers and prosecutors is a popular type of diction. The aspect of cohesiveness of the mind is proven by the formulation of sentences showing the roundness of the elements and having clear links. Furthermore, aspects of the miscarriage caused by sentences uttered by judges, lawyers, or public prosecutors are simple and concise sentences. Abstrak Penelitian ini mengkaji karakteristik ragam bahasa hukum dalam persidangan di Pengadilan Negeri Banda Aceh. Jenis penelitian ini kualitatif dengan pendekatan deskriptif kualitatif. Teknk pengumpulan data dilakukan dengan teknik simak dengan metode rekam catat selama persidangan sumber data penelitian ini terdiri atas ujaran hakim, jaksa penuntut umum, pengacara, terdakwa, dan pengunjung persidangan. Hasil penelitian ini menyimpulkan bahwa dalam persidangan di Pengadilan Negeri Banda Aceh terdapat empat karakteristik dari berbagai bahasa hukum yang terdiri atas (1) keresmian (2) kejelasan makna, (3) kepaduan pikiran, dan (4) kelugasan. Karakteristik ragam bahasa hukum aspek keresmian ditandai dengan penggunaan kata-kata kosakata baku. Aspek kejelasan makna dalam persidangan dibuktikan dengan penggunaan diksi yang mudah dipahami. Diksi yang digunakan oleh hakim, pengacara dan jaksa adalah jenis diksi yang populer. Aspek kepaduan pikiran dibuktikan dengan rumusan kalimat yang menunjukkan kebulatan unsur-unsur dan memiliki keterkaitan yang jelas. Selanjuntya, penerapan aspek kelugasan makna dalam persidangan dibuktikan dengan kalimat yang diucapkan oleh hakim, pengacara, ataupun jaksa penuntut umum merupakan kalimat yang sederhana dan ringkas. Kata Kunci: Ragam Bahasa, Bahasa Hukum, Pengadilan Negeri Banda Aceh